Intermediários do sistema de inovação tecnológica para transição sociotécnica: o caso do biogás no Paraná - Pigatto, Marivanda Bortoloso (2021)
Understanding the importance of recent studies on intermediaries in accelerating transitions, this thesis proposes a new model for analyzing the performance of intermediaries in a technological innovation system. With an exploratory and descriptive qualitative character, documentary and content analyzes of the technological innovation system in Paraná were carried out. The objective is to analyze how intermediaries of the biogas technological innovation system in Paraná have been acting in the process of sociotechnical transition to sustainability, with a case study of CIBiogás – International Center for Renewable Energy Biogas. The results suggest that systemic intermediaries can contribute to the transition to sustainability, facilitating and configuring networks for the development and dissemination of knowledge, entrepreneurial experimentation, influence in search direction, market formation, legitimation, resource mobilization and the development of positive externalities. Interacting with actors, networks and institutions, building trusting relationships and being able to obtain adequate funding for a defined strategic plan.